2014
DOI: 10.1007/s12020-014-0502-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel function for fibroblast growth factor 21: stimulation of NADPH oxidase-dependent ROS generation

Abstract: Fibroblast growth factor 21 (FGF-21) is a major paracrine and endocrine regulator of metabolic homeostasis. Here we demonstrate that FGF-21 is also a potent mediator of innate immunity. Double-staining flow cytometry identified neutrophils and monocytes as the main sources of FGF-21 among circulating leukocytes. Functional assays showed that FGF-21 stimulates phagocytosis and production of reactive oxygen species in neutrophil-like HL-60 cells and monocytic THP-1 cells. The mechanism of action of FGF-21 was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The finding that adipsin-deficiency resulted in a significant increase of the serum levels of FGF-21 and adiponectin is interesting as both adipokines were reported to have metabolic/anti-inflammatory effects and suggested to be instrumental in maintaining joint health [53][54][55][56][57]. FGF-21 is an adipokine/endocrine hormone produced by the liver, adipose tissue and blood cells [58,59], and is reported to be anti-inflammatory and to demonstrate antiaging properties [60,61]. Importantly and related to arthritis, FGF-21 was found to attenuate the collageninduced arthritis by reducing, among other things, some pro-inflammatory cytokines [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that adipsin-deficiency resulted in a significant increase of the serum levels of FGF-21 and adiponectin is interesting as both adipokines were reported to have metabolic/anti-inflammatory effects and suggested to be instrumental in maintaining joint health [53][54][55][56][57]. FGF-21 is an adipokine/endocrine hormone produced by the liver, adipose tissue and blood cells [58,59], and is reported to be anti-inflammatory and to demonstrate antiaging properties [60,61]. Importantly and related to arthritis, FGF-21 was found to attenuate the collageninduced arthritis by reducing, among other things, some pro-inflammatory cytokines [55].…”
Section: Discussionmentioning
confidence: 99%
“…Although a relationship between the expression of adipsin and FGF-21 has been reported [62], the regulatory factors at play still remain to be determined. FGF-21 is known to be regulated by a number of metabolic factors, nutrients, and oxidative stress [58,63,64], and involved in the regulation of glucose and lipid metabolism [65][66][67][68]. This could suggest that the lack of adipsin impacted these metabolic factors.…”
Section: Discussionmentioning
confidence: 99%
“…The same study found no effect of MMP9 genetic depletion on oxygen-induced retinopathy. PEDF promotes metabolism of oxygen radicals by stimulating glutamine synthetase and l-glutamate/l-glutamate transporter levels in neonatal mice with oxygen-induced retinopathy ( 96 ). Modifying PEDF levels through intravitreal drug injections has been investigated as a possible approach to prevent ROP.…”
Section: Pigment Epithelium Derived Factormentioning
confidence: 99%
“…Among peripheral blood leukocytes, FGF21 was highly expressed in monocytes and neutrophils ( 81 ). By increasing the expression of GLUT-1, FGF21 upregulated the ability to uptake glucose in activated monocytes, which can be beneficial in immune activation ( 82 ).…”
Section: Fgf21 In Inflammationmentioning
confidence: 99%